2008
DOI: 10.1111/j.1467-7717.2008.01048.x
|View full text |Cite
|
Sign up to set email alerts
|

Responding to crises and disasters: the role of risk attitudes and risk perceptions

Abstract: Discussions are taking place both in the United States and in Europe about how governments should respond to both disasters and crises, and how citizens' non-desirable behaviour might be managed with respect to such disasters. Here we examine the role that risk attitudes and risk perceptions play in decision making behaviour of individuals in times of crises and disasters and how knowledge about individual behaviour and its drivers may be helpful when developing policy. The proposed framework complements the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 26 publications
(21 reference statements)
1
31
0
Order By: Relevance
“…They found that in most of the studies there were significant correlations between risk perception and seismic adjustment, though the results were not consistent. Some newer studies also found that people's risk attitudes and risk perceptions are the main drivers of their decision-making behavior in times of crises and disasters (Pennings and Grossman 2008). Similar results were reported by other empirical studies-correlation and regression analyses indicated that disaster preparedness was positively associated with flood risk perception (Miceli, Sotgiu, and Settanni 2008).…”
Section: Individual Factorssupporting
confidence: 79%
“…They found that in most of the studies there were significant correlations between risk perception and seismic adjustment, though the results were not consistent. Some newer studies also found that people's risk attitudes and risk perceptions are the main drivers of their decision-making behavior in times of crises and disasters (Pennings and Grossman 2008). Similar results were reported by other empirical studies-correlation and regression analyses indicated that disaster preparedness was positively associated with flood risk perception (Miceli, Sotgiu, and Settanni 2008).…”
Section: Individual Factorssupporting
confidence: 79%
“…(1) is specified as follows in Eq. (2). βX = β 1 cumy + β 2 age1 + β 3 age2 + β 4 cd + β 5 cds +β 6 sex +β 7 sin+β 8 log(inc) (2) where, cumy is the cumulative volume of bottled water purchased from April 2009 to February 2011; age1 is a dummy variable taking a value of one for individuals aged 34 years or younger, otherwise zero; age2 is a dummy variable taking a value of one for individuals aged from 35 to 49 years, otherwise zero; cd is a dummy variable taking a value of one for individuals with children, otherwise zero; sex is a dummy variable taking a value of one for men, otherwise zero; sin is a dummy variable taking a value of one for single (unmarried) individuals, otherwise zero; and log(inc) is the natural log of income per household member 5 .…”
Section: Model and Datamentioning
confidence: 99%
“…This resulted in the absence of bottled water on supermarket shelves 1 . Consumer reactions to the natural disaster are also analyzed [1,2]. This paper analyzed who purchased more bottled water around the time of the earthquake using scanned individual data.…”
mentioning
confidence: 99%
See 2 more Smart Citations